Sinergitas Desa Dinas dengan Desa Adat dalam Penanganan Pandemi Covid-19 di Desa Tibubeneng, Kecamatan Kuta Utara, Kabupaten Badung. - Ni Made Melly Deni Kiara Putri; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
All parties in Bali play a role in preventing the Covid-19 pandemic, Traditional Villages and Service Villages are the spearhead of the government system in Bali. The formulation of the problems in this study is 1) How is the synergy of Service Village and Traditional Village to accelerate the handling of the Covid-19 pandemic in Tibubeneng Village, North Kuta Subdistrict, Badung Regency? 2) How are the obstacles of Service Village and Traditional Village to accelerate the handling of the Covid-19 pandemic in Tibubeneng Village, North Kuta Subdistrict, Badung Regency? The research method used in this study is empirical legal research with an approach to the problem using a fact approach and a sociological approach. Synergy Service Village and Traditional Village in Tibubeneng Village to the handling of Covid-19 can be seen in the regulation which is passed down by the regional government. The results indicated Synergy Service Village and Traditional Village in the Tibubeneng Village were going well, but there were still obstacles. Sanctions for traditional karma and karma tamiu that violate the appeal from the traditional village listed in the pararem must continue to be executed further.